Effectiveness of Knowledge Management on Customer Relationship Management in Hotel Business Performance - SRIVASTAVA, Sanjiv Kumar; CHANDRA, Bibhas; SINHA, Anand Prasad (Journal of Environmental Management and Tourism, 2019)
Knowledge Management (KM) and Customer Relationship Management (CRM) have become indispensable strategic tool for the Hotel sector to gain competitive edge in the marketing environment. Hotels sustain and survive by exploiting customer knowledge for creating relationship to improve customer satisfaction, loyalty and thus, leading to better business performance. Hotel industries heavily rely on effective relationship management and CRM essentially depends upon effective and efficient utilization of knowledge resource. Therefore, effectiveness of customer relationship management depends upon effectiveness of Integration of knowledge management process with CRM process. Hotel managers are quick to realise the importance of CRM based marketing strategy to sustain and gain edge over the competitors. The paper presents a review study of literature regarding effectiveness of KM and CRM on hotel business performance with a proposal of an integrated conceptual framework between KM and CRM process.